(Background papers submitted by the National Committee of Sweden for the Programme on Man and the Biosphere) - Expert Panel on Project 2: Ecological Effects of Different Land Uses and Management Practices on Temperate and Mediterranean Forest Landscapes, Paris, 1974 (1974)
Working papers submitted under the MAB Programme by Sweden on forest ecosystems and landscape, with particular reference to the temperate zone - Describes characteristics of fauna and human activities effects on the taiga, compares ecological conditions during periods of agricultural development and industrialization, deals with primary and secondary forest resources